Parental exposure to environmental concentrations of diuron leads to aneuploidy in embryos of the Pacific oyster, as evidenced by fluorescent in situ hybridization - Barranger, Audrey; Benabdelmouna, Abdellah; Degremont, Lionel; Burgeot, Thierry; Akcha, Farida (Aquatic Toxicology, 2015)
Changes in normal chromosome numbers (i.e. aneuploidy) due to abnormal chromosome segregation may arise either spontaneously or as a result of chemical/radiation exposure, particularly during cell division. Coastal ecosystems are continuously subjected to various contaminants originating from urban, industrial and agricultural activities. Genotoxicity is common to several families of major environmental pollutants, including pesticides, which therefore represent a potential important environmental hazard for marine organisms. A previous study demonstrated the vertical transmission of DNA damage by subjecting oyster genitors to short-term exposure to the herbicide diuron at environmental concentrations during gametogenesis. In this paper, Fluorescent in situ hybridization (FISH) was used to further characterize diuron-induced DNA damage at the chromosomal level. rDNA genes (5S and 18-5.8-28S), previously mapped onto C. gigas chromosomes 4, 5 and 10, were used as probes on the interphase nuclei of embryo preparations. Our results conclusively show higher aneuploidy (hypo- or hyperdiploidy) level in embryos from diuron-exposed genitors, with damage to the three studied chromosomal regions. This study suggests that sexually-developing oysters are vulnerable to diuron exposure, incurring a negative impact on reproductive success and oyster recruitment.